Filamentous fungi in cheese production - Metin, Banu (IGI GLOBAL, 2018)
Filamentous fungi play important roles in the production of a variety of cheeses. The most famous are the blue cheeses, such as Roquefort or Gorgonzola, in which Penicillium roqueforti is the principal mold, and the moldy soft cheeses, such as Camembert or Brie, in which production involves Penicillium camemberti. There are also other filamentous fungi associated with certain types of cheeses, such as Mucor spp., Trichothecium roseum, and Fusarium domesticum in Saint Nectaire, Sporendonema casei in Cantal, Salers and Rodez cheeses, Scopulariopsis species in various French and Austrian cheeses, and Mucor mucedo and Mucor racemosus in the traditional Norwegian cheese Gamalost. These fungi are either inoculated on the cheese as a starter culture or stand out in mixed cultures during spontaneous fermentation. This chapter reviews the filamentous fungi used to produce different kinds of cheeses in terms of taxonomy, physiology, ecology, and mycotoxins, and the microbiological or biochemical effects of these fungi on cheese production.
WOS: 000468898100015